Investigation of mechanical properties and micromechanisms of saline soil modified with synthetic fibers - Zhixin Liu; Dongmei Chen; Jili Qu (PLoS ONE, 2025)
To study the mechanical properties and microscopic morphology of salt-affected soil after being improved by fiber types and contents, the article analyzes the unconfined compressive strength and shear strength of the sulfate-affected soil in Kashi, Xinjiang, China, which four different fiber contents have improved. Some samples are tested by scanning electron microscope (SEM) and nuclear magnetic resonance (NMR) microanalysis. The article selects the sample with the highest improved unconfined compressive strength for dry-wet cycling and dissolution test. The results show that polypropylene, polyester, and glass fiber can increase the maximum dry density of salt-affected soil. The unconfined compressive strength of the soil with 1% polyester fiber and 8% silica fume reinforcement is the highest, which is 1.98 times that of the original soil. The unconfined compressive strength of the soil with 1% polyester fiber reinforcement is the largest, 1.43 times that of the original soil. The unconfined compressive strength of the soil with 5% and 7% glass fiber reinforcement is relatively large, 1.56 and 1.57 times that of the original soil, respectively. The cohesion of the original soil is the largest. The internal friction angle of the soil with 6% glass fiber reinforcement is the largest. In addition, the addition of synthetic fibers can significantly reduce the dissolution coefficient of salt-affected soil, especially glass fibers. Through SEM and NMR analysis, it is found that fibers form a good clamping action with soil particles, and some fibers have a tight bond with the soil, reducing the porosity of the soil.